Introduction to a Future Way of Thought On Marx and Heidegger - Axelos, Kostas; Elden, Stuart (meson press, 2015)
"Technologists only change the world in various ways in generalized indifference; the point is to think the world and interpret the changes in its unfathomability, to perceive and experience the difference binding being to the nothing." Anticipating the age of planetary technology Kostas Axelos, a Greek-French philosopher, approaches the technological question in this book, first published in 1966, by connecting the thought of Karl Marx and Martin Heidegger. Marx famously declared that philosophers had only interpreted the world, but the point was to change it. Heidegger on his part stressed that our modern malaise was due to the forgetting of being, for which he thought technological questions were central. Following from his study of Marx as a thinker of technology, and foreseeing debates about globalization, Axelos recognizes that technology now determines the world. Providing an introduction to some of his major themes, including the play of the world, Axelos asks if planetary technology requires a new, a future way of thought which in itself is planetary.